An assessment of the screening method to evaluate vaccine effectiveness: the case of 7-valent pneumococcal conjugate vaccine in the United States. - Adam L Cohen; Thomas Taylor; Monica M Farley; William Schaffner; Lindsey J Lesher; Kenneth A Gershman; Nancy M Bennett; Arthur Reingold; Ann Thomas; Joan Baumbach; Lee H Harrison; Susan Petit; et al. (PLoS ONE, 2012)
The screening method, which employs readily available data, is an inexpensive and quick means of estimating vaccine effectiveness (VE). We compared estimates of effectiveness of heptavalent pneumococcal conjugate vaccine (PCV7) against invasive pneumococcal disease (IPD) using the screening and case-control methods. Cases were children aged 19-35 months with pneumococcus isolated from normally sterile sites residing in Active Bacterial Core surveillance areas in the United States. Case-control VE was estimated for 2001-2004 by comparing the odds of vaccination among cases and community controls. Screening-method VE for 2001-2009 was estimated by comparing the proportion of cases vaccinated to National Immunization Survey-derived coverage among the general population. To evaluate the plausibility of screening-method VE findings, we estimated attack rates among vaccinated and unvaccinated persons. We identified 1,154 children with IPD. Annual population PCV7 coverage with ≥1 dose increased from 38% to 97%. Case-control VE for ≥1 dose was estimated as 75% against all-serotype IPD (annual range: 35-83%) and 91% for PCV7-type IPD (annual range: 65-100%). By the screening method, the overall VE was 86% for ≥1 dose (annual range: -240-70%) against all-serotype IPD and 94% (annual range: 62-97%) against PCV7-type IPD. As cases of PCV7-type IPD declined during 2001-2005, estimated attack rates for all-serotype IPD among vaccinated and unvaccinated individuals became less consistent than what would be expected with the estimated effectiveness of PCV7. The screening method yields estimates of VE that are highly dependent on the time period during which it is used and the choice of outcome. The method should be used cautiously to evaluate VE of PCVs.